Variable Sensitivity of SARS-CoV-2 Molecular Detection in European Expert Laboratories: External Quality Assessment, June and July 2020 - Fischer, Carlo (J Clin Microbiol, 2021)
During the ongoing coronavirus disease 2019 (COVID-19) outbreak, robust detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a key element for clinical management and to interrupt transmission chains. We organized an external quality assessment (EQA) of molecular detection of SARS-CoV-2 for European expert laboratories. An EQA panel composed of 12 samples, containing either SARS-CoV-2 at different concentrations to evaluate sensitivity or other respiratory viruses to evaluate specificity of SARS-CoV-2 testing, was distributed to 68 laboratories in 35 countries. Specificity samples included seasonal human coronaviruses hCoV-229E, hCoV-NL63, and hCoV-OC43, as well as Middle East respiratory syndrome coronavirus (MERS-CoV), SARS-CoV, and human influenza viruses A and B. Sensitivity results differed among laboratories, particularly for low-concentration SARS-CoV-2 samples. Results indicated that performance was mostly independent of the selection of specific extraction or PCR methods.